Analisis Biaya Cadangan Risiko Pinjaman dan Cadangan Risiko Pinjaman Dalam Laporan Auditor Independen Unit Pengelola Keuangan (Studi Kasus: Badan Keswadayaan Masyarakat di Kabupaten Bantul Provinsi DIY) - Kurniawan Kurniawan; Dody Hapsoro (Jurnal Akuntansi, 2016)
This study examines whether there are differences in the cost of the loan risk reserves and the loan risk reserves between audit results data and financial reporting. The research sample consisted of the audit results report on 50 BKM (Badan Keswadayaan Masyarakat) in Kabupaten Bantul Provinsi Daerah IstimewaYogyakarta whichhave been audited by Budiman, Wawan, Pamudji and Partners Public Accounting Firmin 2014. This study found that the cost of the loan risk allowances and loan risk allowances between audit result and reporting differed significantly. The study concluded that almost all of BKM not charge cost and reserve risk of the loan according collectibility list that is used as the source of the audit resultscalculation. Keywords: Cost of the loan risk reserves, loan risk reserves, audit results, reporting.